1988
DOI: 10.1246/bcsj.61.3217
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonylation of Biomolecules with Inorganic Diphosphonate. II. Phosphonylation of Phosphate Groups on Nudeoside 5′-Monophosphates, Deoxynudeoside 5′-Monophosphates, and Sugar Phosphates

Abstract: Inorganic diphosphonate phosphonylated predominantly phosphate groups on nucleoside 5′-monophosphates (=NMP’s: AMP, GMP, IMP, CMP, and UMP), deoxynudeoside 5′-monophosphates (=dNMP’s: dAMP and dTMP), and sugar phosphates (=SP’s: GlclP, Glc6P, and Rib5P) in aqueous solutions under mild conditions (50–70 °C, pH 6). The chemical structures of phosphonylated products were discussed on their 31P NMR spectra and high-performance liquid chromatograms. The main phosphonylated products from NMP’s and dNMP’s were analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…One of the authors reported the phosphonylation of nucleoside 5'-monophosphate 7 and nucleoside 5'-diphosphate 8 by DP. According to Scheme 1, the phosphonyl transfer reaction was performed at 5'-monophosphate of the β-D-ribofuranosyl unit to form an H-phosphonate analogue of 5'-ADP.…”
Section: Figure 1 Structure Of L-dopamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the authors reported the phosphonylation of nucleoside 5'-monophosphate 7 and nucleoside 5'-diphosphate 8 by DP. According to Scheme 1, the phosphonyl transfer reaction was performed at 5'-monophosphate of the β-D-ribofuranosyl unit to form an H-phosphonate analogue of 5'-ADP.…”
Section: Figure 1 Structure Of L-dopamentioning
confidence: 99%
“…A previous work indicated that the phosphonylation product of adenosine 5'-monophosphate 7 with DP is H-phosphonate esters with a P-H bond.…”
Section: Reaction Of 3'4'-dihydroxy-l-phenylalanine (L-dopa) With Dpmentioning
confidence: 99%
“…Yamamoto et al previously studied that adenosine 5'-monophosphate was phosphonylated by DP to give an analogue of adenosine 5'-diphosphate (5'-ADP) 11 . Later, they have reported the phosphonylation of nucleoside 5'-diphosphate with DP in order to form H-phosphonate analogues of nucleotide 5'-triphosphate (5'-NTP) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its unique structure, biologically important compounds having a hydroxyl group can be phosphonylated by DP. Baba et al reported the phosphonylation of nucleoside 5'-monophosphate 12 and nucleoside 5'-diphosphate 13 with DP to form H-phosphonate analogues of 5'-ADP and 5'-ATP. More recently, our group studied the phosphonylation of salicin with DP 14 .…”
Section: Introductionmentioning
confidence: 99%